Pengaruh Catalytic Converter Dari Bahan Kuningan Dengan Ketebalan 0,3 mm Terhadap Emisi Gas Buang Kendaraan Pada Motor Honda Supra 2015 - Budiyono Budiyono (Politeknik Negeri Padang, 2020)
There are two methods to reduce exhaust emissions in a motorized vehicle, namely by improving fuel and motorbike technology in such a way that better combustion occurs and produces lower emissions and by the addition of exhaust emission control devices or devices. Catalytic Converter is a device used as an exhaust gas emission control that is placed after the exhaust manifold on a motor vehicle exhaust system. The purpose of this study was to determine how the influence of the use of catalytic converters of brass material to reduce CO and HC gas levels in motor vehicles. Tests carried out using a gas analyzer to determine the value of CO and HC concentrations. Exhaust gas testing is carried out in two stages, namely exhaust emission test with standard exhaust and exhaust emission test with catalytic converter with variations of engine speed 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm. From the results of the study it was found that the influence of the use of catalytic converters of brass with a thickness of 0.3 mm with the fin model experienced a decrease in the level of exhaust gas emissions most effectively at 1500 rpm engine speed ie CO value decreased 1.82% from 3.96% to 2.14% and HC values ​​decreased by 4,412 ppm from 9,999 ppm down to 5,587 ppm. So motor vehicles using a catalytic converter made of brass with a thickness of 0.3 mm will be able to reduce CO exhaust emissions by 2.14% and HC by 3.96%